Editorial: Wellbeing and work-integrated learning - Hay K; Fleming J (Work-Integrated Learning New Zealand, 2025)
Higher Education Institutions (HEIs) have important responsibilities for the duty of care of their students, and to ensure the wellbeing of students is kept front and center of curriculum and institutional developments. While the focus has primarily been on physical campuses, it is critical that these responsibilities extend to off campus activities, such as work-integrated learning (WIL). This special issue includes 11 articles focusing on the wellbeing of WIL students, with many authors drawing on empirical research. Key themes include students’ understanding of WIL wellbeing; students’ experiences of WIL and wellbeing; strategies for preparing WIL students to support wellbeing; understanding the wellbeing needs of diverse WIL students; and the important role of workplace supervisors in supporting WIL wellbeing. Several authors amplify the voices of students and all share thought-provoking teaching and curriculum strategies. All WIL stakeholders have a responsibility to support the learning success and wellbeing of students.
Keywords: Wellbeing; mental health; work-integrated learning; inclusion; risk; student voice; hardship